Preparation and In Vitro Behavior of a Poly(lactic acid)-Fiber/Hydroxyapatite Composite Sheet - Yasuhiro Tanimoto; Norihiro Nishiyama (Advances in Materials Science and Engineering)
This paper describes the processing and in vitro behavior of a poly(lactic acid) (PLA)-fiber/hydroxyapatite (HA) composite sheet consisting of a knitted PLA-fiber sheet and HA powder for bone tissue engineering. Type I collagen was used as a binding agent to combine the PLA fibers and the HA powder. Precipitate formation in Hanks' balanced salt (HBS) solution was monitored to evaluate the in vitro apatite formation ability of the PLA-fiber/HA composite sheet. Precipitate formation was observed on the surface of the PLA-fiber/HA composite sheet after immersion in HBS solution for only 1 day, while no precipitate formation was observed on the PLA-fiber sheet without HA as a control. In conclusion, a PLA-fiber/HA composite sheet for use as a scaffold was successfully prepared. Within the limitations of this investigation, we confirmed that the PLA-fiber/HA composite sheet has a high apatite formation activity compared with the PLA-fiber sheet and represents a promising material for use as a scaffold.